Polymeric binders for titanium dioxide-containing aqueous coating compositions based on 2-octyl acrylate, n-butyl acrylate and methyl methacrylate

JP2025505613APending Publication Date: 2025-02-28BASF SE
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024546183
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-04
Filing Date
2023-02-03
Publication Date
2025-02-28

AI Technical Summary

Benefits of technology

【0012】 驚くべきことに、2-オクチルアクリレート、n-ブチルアクリレート(BA)およびメチルメタクリレート(MMA)に基づく本発明のコポリマーは、同等に配合された建築用コーティング中のn-ブチルアクリレートおよびメチルメタクリレートに基づくコポリマーと比較して、改善された耐擦過性、改善された光沢および改善された増粘効率、ならびに同等の不透明度、接着性、耐汚染性および汚れ付着性をもたらすことが見出された。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025505613000001
    Figure 2025505613000001
  • Figure 2025505613000002
    Figure 2025505613000002
  • Figure 2025505613000003
    Figure 2025505613000003
Patent Text Reader

Abstract

An aqueous polymer latex obtained by polymerizing, optionally in the presence of a seed latex, a monomer composition M by radical emulsion polymerization, the monomer composition M comprising, based on the total weight of the monomer composition M: a) 0.5 to 30% by weight of 2-octyl acrylate; b) 25 to 55% by weight of n-butyl acrylate; c) 35 to 65% by weight of methyl methacrylate; d) 0 to 5% by weight of one or more monoethylenically unsaturated carboxylic acids; e) 0 to 5% by weight of one or more monoethylenically unsaturated carboxylic acid amides, f) 0 to 10% by weight of one or more further ethylenically unsaturated nonionic monomers different from the monomers a), b), c), d), and e). 1. A water-based polymer latex comprising:
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aqueous polymer latex obtained by polymerizing a monomer composition M comprising 2-octyl acrylate, n-butyl acrylate and methyl methacrylate. The present invention further relates to the use of the aqueous polymer latex as a binder in an aqueous coating composition containing a titanium dioxide pigment, and the present invention also relates to an aqueous coating composition containing the aqueous polymer latex and the titanium dioxide pigment. [Background technology]

[0002] Titanium dioxide (TiO2) is frequently used as a pigment in water-based coating compositions such as latex paints. In addition to whiteness, TiO2 imparts opacity or hiding power, respectively, to the coating, meaning that the coating is opaque and conceals and covers the underlying or substrate surface to which it is applied.

[0003] WO 2017 / 191167 discloses an aqueous polymer latex for use as a binder in an aqueous coating composition containing titanium dioxide pigment. The aqueous polymer latex is obtained by polymerizing a monomer composition M by radical emulsion polymerization using a specific supply method, the monomer composition M being a) 80 to 99.95% by weight of an ethylenically unsaturated monomer M1 based on the total weight of the monomer composition M, 20 -C5-C alkyl esters and methacrylic acid 20 - a mixture of at least one monomer M1a selected from the group consisting of alkyl esters; and at least one monomer M1b selected from vinyl aromatic monomers and C1-C4-alkyl esters of methacrylic acid; b) 0.05 to 5 wt. %, based on the total weight of the monomer composition M, of one or more monoethylenically unsaturated monomers M2 selected from monoethylenically unsaturated monocarboxylic acids having 3 to 6 carbon atoms and monoethylenically unsaturated dicarboxylic acids having 4 to 6 carbon atoms; c) 0 to 20% by weight of a non-ionic monomer M3 different from the monomer M1 It consists of:

[0004] Preferred monomers M1a are C2-C 10 -alkyl esters, in particular ethyl acrylate, n-butyl acrylate, n-hexyl acrylate, n-octyl acrylate, 2-ethylhexyl acrylate and 2-propylheptyl acrylate. Preferred monomers M1b are vinyl aromatic monomers and mixtures of vinyl aromatic monomers with C1-C4-alkyl esters of methacrylic acid. In particular, monomers M1b are selected from styrene and mixtures of styrene with methyl methacrylate. Preferred monomers M2 are acrylic acid and methacrylic acid. Preferred monomers M3 are hydroxy-C2-C4-alkyl esters of acrylic acid and methacrylic acid.

[0005] WO 2014 / 207389 relates to the use of a polymer obtained from the polymerization of 2-octyl acrylate of renewable origin and optionally at least one other monomer as a binder in or for the manufacture of a coating composition. The other monomer is preferably selected from esters of ethylenically unsaturated mono- and dicarboxylic acids, in particular methyl methacrylate and n-butyl acrylate, vinyl aromatic monomers, more particularly styrene, and mixtures thereof. This document discloses a transparent coating.

[0006] WO 2016 / 128574 relates to an aqueous polymer emulsion comprising at least 30% by weight of a vinyl copolymer (A), the vinyl copolymer being (I) 10 to 90% by weight of 2-octyl acrylate monomer; (II) 10 to 90 weight percent of at least one itaconic acid ester monomer; and (III) 0 to 80% by weight of an ethylenically unsaturated monomer other than (I) and (II). Includes.

[0007] Other ethylenically unsaturated monomers (III) include acrylic acid and / or methacrylic acid and monomers selected from methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, styrene, and combinations thereof.

[0008] WO 2018 / 007325 discloses an aqueous emulsion comprising at least 30% by weight of one or more vinyl copolymers (A), said one or more vinyl copolymers (A) comprising the following monomers: (I) a total amount of isobornyl methacrylate and 2-octyl acrylate of at least 30% by weight (the weight ratio of isobornyl methacrylate to 2-octyl acrylate is 5:95 to 95:5); (II) up to 70% by weight of at least one ethylenically unsaturated monomer other than 2-octyl acrylate and isobornyl methacrylate. The other ethylenically unsaturated monomers (II) include acrylic acid and / or methacrylic acid and monomers selected from methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, styrene and combinations thereof. This document discloses a transparent coating. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] International Publication No. 2017 / 191167 Brochure [Patent Document 2] International Publication No. 2014 / 207389 Brochure [Patent Document 3] International Publication No. 2016 / 128574 Brochure [Patent Document 4] International Publication No. 2018 / 007325 Brochure Summary of the Invention [Problem to be solved by the invention]

[0010] The object of the present invention is to provide alternative methyl methacrylate (MMA) copolymers with glass transition temperatures comparable to those based on methyl methacrylate and n-butyl acrylate (BA), suitable as binders in architectural coatings containing TiO2 with good abrasion resistance, thickening efficiency, gloss and opacity, as well as excellent adhesion, stain resistance and low dirt adhesion. [Means for solving the problem]

[0011] This object is solved by an aqueous polymer latex obtainable by polymerizing, by radical emulsion polymerization, a monomer composition M, which comprises, based on the total weight of the monomer composition M, a) 0.5 to 30% by weight of 2-octyl acrylate; b) 25 to 55% by weight of n-butyl acrylate; c) 35 to 65% by weight of methyl methacrylate d) 0 to 5% by weight of one or more monoethylenically unsaturated carboxylic acids; e) 0 to 5% by weight of one or more monoethylenically unsaturated carboxylic acid amides, f) 0 to 10% by weight of one or more further ethylenically unsaturated nonionic monomers different from the monomers a), b), c), d) and e). Includes.

[0012] Surprisingly, it has been found that the copolymers of the present invention based on 2-octyl acrylate, n-butyl acrylate (BA) and methyl methacrylate (MMA) provide improved scratch resistance, improved gloss and improved thickening efficiency, as well as comparable opacity, adhesion, stain resistance and dirt adhesion, compared to copolymers based on n-butyl acrylate and methyl methacrylate in comparably formulated architectural coatings.

[0013] Preferably, 2-octyl acrylate, n-butyl acrylate and methyl methacrylate comprise at least 95% by weight of the monomer composition M. For example, 2-octyl acrylate may be present in an amount of 1 to 15% by weight of the monomer mixture M, n-butyl acrylate may be present in an amount of 25 to 55% by weight, and methyl methacrylate may be present in an amount of 40 to 65% by weight.

[0014] Preferably, the monoethylenically unsaturated carboxylic acid d) is selected from the group consisting of acrylic acid, methacrylic acid, maleic acid, the half methyl ester of maleic acid, the half ethyl ester of maleic acid, citraconic acid, the half methyl ester of citraconic acid, itaconic acid, the half methyl ester of itaconic acid, 3-pentenoic acid, 2-butenoic acid, fumaric acid, the half methyl ester of fumaric acid, the half ethyl ester of fumaric acid, halogenated acrylic acids and halogenated methacrylic acids. Most preferably, the monomer d) is selected from acrylic acid, methacrylic acid and itaconic acid.

[0015] Preferably, the monoethylenically unsaturated carboxylic acid amide e) is selected from the group consisting of acrylamide, methacrylamide, N-methylacrylamide, N-ethylacrylamide, N-propylacrylamide, N-isopropylacrylamide, N-butylacrylamide, N-methylmethacrylamide, N-ethylmethacrylamide, N-propylmethacrylamide, N-isopropylmethacrylamide and N-butylmethacrylamide. Most preferably, the monomer e) is selected from acrylamide and methacrylamide.

[0016] In a preferred embodiment, monomer d) is present in an amount of 0.1 to 4 wt.-%. In a more preferred embodiment, monomer d) is present in an amount of 0.5 to 3 wt.-%, even more preferably 0.5 to 2 wt.-%, based on the total weight of the monomer composition.

[0017] In a further preferred embodiment, monomer e) is present in an amount of 0.1 to 4 wt.-%. In a more preferred embodiment, monomer e) is present in an amount of 0.5 to 3 wt.-%, even more preferably 1 to 3 wt.-%, based on the total weight of the monomer composition.

[0018] Monomer f), if present, is preferably a C2-C acrylic acid 10 -alkyl esters, in particular tert-butyl acrylate, 2-propylheptyl acrylate, n-octyl acrylate, 2-ethyl-hexyl acrylate, C1-C4-alkyl esters of methacrylic acid different from methyl methacrylate, in particular 2-ethylhexyl methacrylate, butyl methacrylate and tert-butyl methacrylate, and vinyl aromatic monomers, in particular styrene.

[0019] In a further preferred embodiment, monomer f) is absent in the monomer composition M.

[0020] In a preferred embodiment, the monomer composition M is a) 1 to 15% by weight, more preferably 3 to 12% by weight, of 2-octyl acrylate; b) 25 to 55% by weight, more preferably 30 to 50% by weight, of n-butyl acrylate; c) 40 to 65% by weight, more preferably 40 to 60% by weight, of methyl methacrylate; d) 0 to 5% by weight of one or more monoethylenically unsaturated carboxylic acids; e) 0 to 5% by weight of one or more monoethylenically unsaturated carboxylic acid amides It comprises or consists of:

[0021] In a more preferred embodiment, the monomer composition M is a) 1 to 15% by weight, more preferably 3 to 12% by weight, of 2-octyl acrylate; b) 25 to 55% by weight, more preferably 30 to 50% by weight, of n-butyl acrylate; c) 40 to 65% by weight, more preferably 40 to 60% by weight, of methyl methacrylate; d) 0 to 5% by weight of one or more monoethylenically unsaturated carboxylic acids selected from acrylic acid, methacrylic acid and itaconic acid; e) 0 to 5% by weight of one or more monoethylenically unsaturated carboxylic acid amides selected from acrylamide and methacrylamide It comprises or consists of:

[0022] In a particularly preferred embodiment, the monomer composition M is a) 3 to 12% by weight of 2-octyl acrylate; b) 30 to 50% by weight of n-butyl acrylate; c) 40 to 60% by weight of methyl methacrylate; d) 0 to 5% by weight of acrylic acid; e) 0 to 5% by weight of acrylamide It consists of:

[0023] In some preferred embodiments, the monomer composition M is a) 3 to 12% by weight of 2-octyl acrylate; b) 30 to 50% by weight of n-butyl acrylate; c) 40 to 60% by weight of methyl methacrylate; d) 0.1 to 4% by weight of a monoethylenically unsaturated carboxylic acid selected from acrylic acid, methacrylic acid and itaconic acid; e) 0.1 to 4% by weight of a monoethylenically unsaturated carboxylic acid amide selected from acrylamide and methacrylamide It consists of:

[0024] In some preferred embodiments, the monomer composition M is a) 3 to 12% by weight of 2-octyl acrylate; b) 30 to 50% by weight of n-butyl acrylate; c) 40 to 60% by weight of methyl methacrylate; d) 0.5 to 3% by weight of acrylic acid; e) 0.5 to 3% by weight of acrylamide It consists of:

[0025] In some preferred embodiments, at least a portion of the 2-octyl acrylate of component a) is produced from renewable raw materials, i.e. at least a portion of the 2-octyl acrylate of component a) is a bio-based 2-octyl acrylate obtained partially or completely from renewable raw materials. Also, a mixture of 2-octyl acrylate obtained from fossil raw materials and 2-octyl acrylate obtained partially or completely from renewable raw materials can be used.

[0026] 2-Octyl acrylate can be synthesized, for example, by esterification of acrylic acid with 2-octanol, or by transesterification of, for example, methyl acrylate or ethyl acrylate with 2-octanol.

[0027] Preferably, the bio-based 2-octyl acrylate acrylate is obtained by reaction of 2-octanol with acrylic acid, whereby 2-octanol and / or acrylic acid and / or methyl acrylate and / or ethyl acrylate are at least partially produced from renewable raw materials.

[0028] Bio-based 2-octanol from renewable feedstocks can be obtained from castor oil.

[0029] Acrylic acid from renewable raw materials can be prepared, for example, according to WO 2006 / 092272 or DE 102006039203 or EP 2 922 580.

[0030] It is also possible, according to the mass balance approach, that at least a part of the extracts used to synthesize the monomer composition M originate from renewable raw materials. Thus, in addition to fossil raw materials, renewable raw materials such as bionaphtha (for example those described in EP 2 290 045 or EP 2 290 034) also enter chemical production systems such as steam crackers. The renewable raw materials are converted into products along the chemical value chain, such as acrylic acid, butyl acrylate, methyl methacrylate or acrylamide. The content of renewable materials in these products can be defined and allocated to these products by the mass balance approach.

[0031] The preparation process of the polymer latex is carried out according to well-known processes of the radical emulsion polymerization technique. The conditions necessary for carrying out the free-radical emulsion polymerization of the monomers M can be found, for example, in the first cited prior art and in "Emulsions-polymerisation" [Emulsion Polymerisation] in Encyclopedia of Polymer Science and Engineering, vol. 8, pages 659 ff. (1987); DC Blackley, in High Polymer Latices, vol. 1, pages 35 ff. (1966); H. Warson, The Applications of Synthetic Resin Emulsions, chapter 5, pages 246 ff. (1972); D. Diederich, Chemie in unserer Zeit 24, pages 135 to 142 (1990); Emulsion Polymerisation, Interscience Publishers, New York (1965); DE-A-40 03 422 and Dispersionen synthetischer Hochpolymere [Dispersions of Synthetic High Polymers], F. Holscher, Springer-Verlag, Berlin (1969), are well known to those skilled in the art.

[0032] Free-radical initiated aqueous emulsion polymerization is initiated by free-radical polymerization initiators (free-radical initiators). These are, as a rule, peroxides, azo compounds and redox initiator systems. The peroxides can be inorganic or organic peroxides.

[0033] In certain embodiments, the inorganic peroxide is selected from the group consisting of hydrogen peroxide and persulfates, such as mono- or di-alkali metal or ammonium salts of persulfate, such as mono- and disodium, potassium or ammonium salts.

[0034] In other embodiments, the organic peroxide is selected from the group consisting of alkyl hydroperoxides, such as tert-butyl hydroperoxide, p-menthyl hydroperoxide, or cumyl hydroperoxide, and dialkyl or diaryl peroxides, such as di-tert-butyl or di-cumyl peroxide.

[0035] In a further embodiment, the azo compound is selected from the group consisting of 2,2'-azo-bis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile) and 2,2'-azobis(amidinopropyl) dihydrochloride.

[0036] In a preferred embodiment, the free radical initiator is an inorganic peroxide, particularly a persulfate, and a redox initiator system.

[0037] The oxidizing agents suitable for the redox initiator system are essentially the above-mentioned peroxides.The corresponding reducing agents that can be used are sulfur compounds in a low oxidation state, such as alkali metal sulfites, such as potassium sulfite and / or sodium sulfite, alkali metal hydrogen sulfites, such as potassium hydrogen sulfite and / or sodium hydrogen sulfite, alkali metal metabisulfites, such as potassium metabisulfite and / or sodium metabisulfite, formaldehyde sulfoxylates, such as potassium and / or sodium formaldehyde sulfoxylate, alkali metal salts, in particular the potassium and / or sodium salts of aliphatic sulfinic acids and alkali metal hydrogen sulfides, such as potassium hydrogen sulfide and / or sodium hydrogen sulfide, salts of polyvalent metals, such as iron(II) sulfate, ammonium iron(II) sulfate, iron(II) phosphate, enediols, such as dihydroxymaleic acid, benzoin and / or ascorbic acid, and reduced saccharides, such as sorbose, glucose, fructose and / or dihydroxyacetone.

[0038] In one embodiment, the amount of free radical initiator for the emulsion polymerization M is initially completely charged to the polymerization vessel. However, it is also possible to not charge any free radical initiator at all or to charge only a portion of the free radical initiator, for example up to 40% by weight, in particular up to 30% by weight, based on the total amount of free radical initiator required for the aqueous polymerization medium, and then add the entire amount or the remaining amount, depending on the consumption, in one or more portions batchwise or continuously with a constant or variable flow rate under polymerization conditions during the free radical emulsion polymerization of the monomers M.

[0039] In another preferred embodiment, the free radical aqueous emulsion polymerization of the present invention is carried out at a temperature in the range of 0 to 170° C.; more preferably in the range of 50 to 120° C., most preferably in the range of 60 to 120° C., and in particular, the free radical aqueous emulsion polymerization of the present invention is carried out at a temperature in the range of 70 to 110° C. The free radical aqueous emulsion polymerization can be carried out at a pressure less than 1 atmosphere, 1 atmosphere, or greater than 1 atmosphere.

[0040] In a particular embodiment, the polymerization is carried out in the presence of a chain transfer agent.The chain transfer agent can be an aliphatic and / or araliphatic halogen compound, such as n-butyl chloride, n-butyl bromide, n-butyl iodide, methylene chloride, ethylene dichloride, chloroform, bromoform, bromotrichloromethane, dibromodichloromethane, carbon tetrachloride, carbon tetrabromide, benzyl chloride, benzyl bromide; an organic thio compound, such as primary, secondary or tertiary aliphatic thiol, such as ethanethiol, n-propanethiol, 2-propanethiol, n-butanethiol, 2-butanethiol, 2-methyl-2-propanethiol, n-pentanethiol, 2-pentanethiol, 3-pentanethiol, 2-methyl-2-butanethiol, 3-methyl-2-butanethiol, n-hexanethiol. , 2-hexanethiol, 3-hexanethiol, 2-methyl-2-pentanethiol, 3-methyl-2-pentanethiol, 4-methyl-2-pentanethiol, 2-methyl-3-pentanethiol, 3-methyl-3-pentanethiol, 2-ethylbutanethiol, 2-ethyl-2-butanethiol, n-heptanethiol and its isomers, n-octanethiol and its isomers, n-nonanethiol and its isomers, n-decanethiol and its isomers, n-undecanethiol and its isomers, n-dodecanethiol and its isomers, n-tridecanethiol and its isomers, substituted thiols such as 2-hydroxyethanethiol, aromatic Thiols, such as benzenethiol, ortho-, meta- or para-methylbenzenethiol, alkyl esters of mercaptoacetic acid (thioglycolic acid), such as 2-ethylhexyl thioglycolate, alkyl esters of mercaptopropionic acid, such as octyl mercaptopropionate, and further, as described in Polymer Handbook, 3rd edition, 1989, J. Brandrup and EHImmergut, John Wiley & Sons, section II, pages 133-141, and aliphatic and / or aromatic aldehydes, such as acetaldehyde, propionaldehyde and / or benzaldehyde, unsaturated fatty acids, such as oleic acid, dienes with non-conjugated double bonds, such as divinylmethane or vinylcyclohexane, or hydrocarbons with easily abstractable hydrogen atoms, such as toluene.

[0041] Generally, the total amount of chain transfer agents, if present, does not exceed 1% by weight, based on the total amount of monomers M.

[0042] Generally, the polymerization is carried out in the presence of a surfactant. The surfactant can be selected from emulsifiers and protective colloids. Protective colloids are understood to mean polymeric compounds with a molecular weight of more than 2000 Daltons, in contrast to emulsifiers, while emulsifiers typically have a lower molecular weight. The surfactant can be anionic or nonionic, or a mixture of nonionic and anionic surfactants.

[0043] Anionic surfactants generally have at least one anionic group selected from phosphate group, phosphonate group, sulfate group and sulfonate group.Anionic surfactants having at least one anionic group are typically used in the form of their alkali metal salts, particularly their sodium salts, or in the form of their ammonium salts.

[0044] In a preferred embodiment, the anionic surfactant is in particular an anionic emulsifier having at least one sulfate or sulfonate group.Similarly, an anionic emulsifier having at least one phosphoric acid or phosphonic acid group can be used as the only anionic emulsifier or in combination with one or more anionic emulsifiers having at least one sulfate or sulfonate group.

[0045] Examples of anionic emulsifiers having at least one sulfate or sulfonate group are, for example, alkyl sulfates, especially C8-C 22 - Alkali metal and ammonium salts of alkyl sulfates, sulfate monoesters of ethoxylated alkanols, especially ethoxylated C8-C 22 - salts of sulfuric acid monoesters of alkanols (preferably with an ethoxylation level (EO level) in the range of 2 to 40), in particular the alkali metal and ammonium salts, and sulfuric acid monoesters of ethoxylated alkylphenols, in particular the ethoxylated C4-C 18 - salts of sulfuric acid monoesters of alkylphenols (EO level preferably 3-40), in particular the alkali metal and ammonium salts, alkylsulfonic acids, in particular C8-C 22 -Salts of alkylsulfonic acids, in particular the alkali metal and ammonium salts, dialkyl esters, in particular di-C1-C2 sulfosuccinic acids 18 - Salts of alkyl esters, in particular the alkali metal and ammonium salts, alkylbenzenesulfonic acids, in particular C4-C 22 - The salts of alkylbenzenesulfonic acids, in particular the alkali metal and ammonium salts, and mono- or disulfonated alkyl-substituted diphenyl ethers, e.g. those having C4-C on one or both aromatic rings. 24 -alkyl groups, particularly the alkali metal and ammonium salts. Examples are U.S. Pat. No. 4,269,749 and Dowfax® 2A1 (Dow Chemical Company).

[0046] In a particularly preferred embodiment, the anionic surfactant is an anionic emulsifier selected from the following group: Alkyl sulfates, especially C8-C 22 the salts of alkyl sulfates, in particular the alkali metal and ammonium salts; Sulfuric acid monoesters of ethoxylated alkanols, especially ethoxylated C8-C 22 - Salts of sulfuric acid monoesters of alkanols, in particular alkali metal salts (preferably with an ethoxylation level (EO level) in the range of 2 to 40) Sulfuric acid monoesters of ethoxylated alkylphenols, especially ethoxylated C4-C 18 - Sulfuric acid monoesters of alkylphenols (EO level preferably 3-40), alkylbenzenesulfonic acids, especially C4-C 22 -sulfuric acid monoesters of alkylbenzenesulfonic acids, and Mono- or disulfonated alkyl-substituted diphenyl ethers, e.g., C4-C on one or both aromatic rings 24 -Bis(phenylsulfonic acid) ethers having alkyl groups.

[0047] Examples of anionic emulsifiers having phosphoric or phosphonic acid groups include, but are not limited to, the following salts selected from the following group: Mono- and dialkyl phosphates, especially C8-C 22 the salts of alkyl phosphates, in particular the alkali metal and ammonium salts, Phosphoric acid monoesters of C2-C3-alkoxylated alkanols, preferably having an alkoxylation level in the range from 2 to 40, in particular in the range from 3 to 30, such as ethoxylated C8-C 22 - Phosphate monoesters of alkanols (preferably with an ethoxylation level (EO level) in the range of 2 to 40), propoxylated C8-C 22 - Phosphate monoesters of alkanols (preferably with a propoxylation level (PO level) of 2-40) and ethoxylated-co-propoxylated C8-C 22 the salts, in particular the alkali metal and ammonium salts, of phosphoric acid monoesters of alkanols, preferably having an ethoxylation level (EO level) in the range from 1 to 20 and a propoxylation level of 1 to 20; Phosphate monoesters of ethoxylated alkylphenols, especially ethoxylated C4-C 18 the salts, in particular the alkali metal and ammonium salts, of phosphoric acid monoesters of alkylphenols (with an EO level preferably between 3 and 40); Alkylphosphonic acids, especially C8-C 22the salts of alkylphosphonic acids, in particular the alkali metal and ammonium salts, Alkylbenzene phosphonic acids, especially C4-C 22 - The salts of alkylbenzenephosphonic acids, in particular the alkali metal and ammonium salts.

[0048] Further suitable anionic surfactants can be found in Houben-Weyl, Methoden der organischen Chemie [Methods of Organic Chemistry], volume XIV / 1, Makromolekulare Stoffe [Macromolecular Substances], Georg-Thieme-Verlag, Stuttgart, 1961, p. 192-208.

[0049] In another preferred embodiment, the surfactant comprises at least one anionic emulsifier having at least one sulfate or sulfonate group. The at least one anionic emulsifier having at least one sulfate or sulfonate group may be the only type of anionic emulsifier. However, a mixture of at least one anionic emulsifier having at least one sulfate or sulfonate group and at least one anionic emulsifier having at least one phosphoric acid or phosphonic acid group may also be used. In such a mixture, the amount of at least one anionic emulsifier having at least one sulfate or sulfonate group is preferably at least 50% by weight based on the total weight of the anionic surfactant used in the method of the present invention. In particular, the amount of the anionic emulsifier having at least one phosphoric acid or phosphonic acid group does not exceed 20% by weight based on the total weight of the anionic surfactant used in the method of the present invention.

[0050] In another preferred embodiment, the surfactant may also comprise one or more non-ionic surface active substances, in particular selected from non-ionic emulsifiers. Suitable non-ionic emulsifiers are, for example, aromatic aliphatic or aliphatic non-ionic emulsifiers, such as ethoxylated mono-, di- and trialkylphenols (EO level: 3-50, alkyl chain: C4-C5, ethylene glycol, propylene ... 10 ), ethoxylates of long-chain alcohols (EO level: 3-100, alkyl chain: C8-C 36 ), as well as polyethylene oxide / polypropylene oxide homopolymers and copolymers. These may contain alkylene oxide units copolymerized in random distribution or in the form of blocks. Very suitable examples are EO / PO block copolymers. Ethoxylates of long-chain alkanols (alkyl chain C1-C 30 , average ethoxylation level 5 to 100) are preferred, and among these, C 12 ~C 20 Particularly preferred are those with alkyl chains and average ethoxylation levels of 5 to 20, as well as ethoxylated monoalkylphenols.Preferably, the surfactant used in the process of the invention comprises less than 60% by weight, in particular not more than 50% by weight, of non-ionic surfactant, based on the total amount of surfactant used in the process of the invention.

[0051] In another embodiment, the surfactant used in the method of the present invention comprises at least one anionic surfactant and at least one nonionic surfactant, and the ratio of anionic surfactant to nonionic surfactant is typically in the range of 0.5:1 to 10:1, in particular 1:1 to 5:1.

[0052] In another preferred embodiment, the surfactant(s) are used in an amount such that the amount of the surfactant(s) is in the range from 0.2% to 5% by weight, in particular in the range from 0.5% to 3% by weight, based on the monomers M to be polymerized.

[0053] The aqueous reaction medium in the polymerization may in principle also contain small amounts (≦5% by weight) of water-soluble organic solvents, such as methanol, ethanol, isopropanol, butanol, pentanol, but also acetone, etc. Preferably, however, the process of the invention is carried out in the absence of such solvents.

[0054] Generally, the resulting aqueous polymer dispersion has a polymer solids content in the range of 10% to 70% by weight, preferably 20% to 65% by weight, more preferably 30% to 60% by weight, and most preferably 40% to 60% by weight, in each case based on the total weight of the aqueous polymer dispersion.

[0055] It has been found to be advantageous to carry out the free radical emulsion polymerization in the presence of a seed latex, which is a polymer latex that is present in the aqueous polymerization medium before the start of the metering of the monomers M. The seed latex can serve to better control the particle size of the final polymer latex obtained in the free radical emulsion polymerization of the present invention.

[0056] Basically, any polymer latex can serve as a seed latex. For the purposes of the present invention, seed latexes in which the polymer particles have a relatively small particle size are preferred. The Z-average particle size of the polymer particles of the seed latex, determined by dynamic light scattering at 20° C., is preferably in the range of 10-80 nm, in particular 10-50 nm. Preferably, the polymer particles of the seed latex are made of ethylenically unsaturated monomers, which are at least 95% by weight, based on the total weight of the monomers forming the seed latex, of C2-C acrylic acid. 10 - alkyl esters, in particular ethyl acrylate, n-butyl acrylate, n-hexyl acrylate, n-octyl acrylate, 2-ethylhexyl acrylate, C1-C4-alkyl esters of methacrylic acid, in particular methyl methacrylate, and vinyl aromatic monomers, in particular styrene.

[0057] For this reason, the seed latex is usually charged to the polymerization vessel before the start of the metering of the monomer M. In particular, the seed latex is charged to the polymerization vessel, followed by the establishment of polymerization conditions and the charging of at least a portion of the free radical initiator to the polymerization vessel before the start of the metering of the monomer M.

[0058] The amount of seed latex, calculated as solids, is often in the range of 0.1 to 10% by weight, in particular 0.5 to 5% by weight, based on the total weight of the monomers Ma), b), c) and d) to be polymerized.

[0059] The present invention also provides i) at least one water-based polymer latex as defined above; and ii) Titanium dioxide pigment The present invention also relates to an aqueous coating composition comprising:

[0060] The present invention also relates to the use of the aqueous polymer latex as a binder in an aqueous coating composition containing titanium dioxide pigment.

[0061] The TiO2 concentration of the aqueous TiO2 pigment slurry or paste used to prepare the aqueous dispersion of the polymer composite is generally in the range of 30% to 85% by weight, often 40% to 80% by weight, in each case based on the total weight of the aqueous TiO2 pigment slurry or paste. The titanium dioxide pigment used to prepare the aqueous dispersion of the polymer composite can be any TiO2 pigment conventionally used in coating compositions, especially aqueous coating compositions. In many cases, TiO2 pigments are used, and the TiO2 particles are preferably in the rutile type. In another preferred embodiment, the TiO2 particles can also be coated, for example with aluminum, silicon and zirconium compounds.

[0062] Generally, the weight ratio of polymer to titanium dioxide pigment is in the range of 0.1:5.0 to 5.0:0.1. Preferably, the weight ratio of polymer to titanium dioxide pigment is in the range of 0.5:5.0 to 5.0:0.5. Especially preferably, the weight ratio of polymer to titanium dioxide pigment is in the range of 0.5:3.0 to 3.0:0.5, in particular 0.5:1.5 to 1.5:0.5.

[0063] Preferably, the titanium dioxide pigment has an average primary particle size in the range of from 0.1 μm to 0.5 μm as determined by light scattering or electron microscopy.

[0064] Generally, the aqueous coating composition further comprises at least one additive selected from the group consisting of thickeners, defoamers, leveling agents, coalescing agents, biocides, wetting or dispersing agents, fillers and coalescing agents.

[0065] The aqueous coating composition can be simply prepared by mixing the TiO2 pigment powder or an aqueous slurry or paste of the TiO2 pigment with the aqueous polymer latex of the present invention, preferably by applying shear to the mixture, for example by using a dissolving agent conventionally used to prepare water-based paints. It is also possible to prepare an aqueous slurry or paste of the TiO2 pigment and the aqueous polymer latex of the present invention, which can then be incorporated or mixed with the further polymer latex of the present invention or any other polymer latex binder.

[0066] Aqueous dispersions of polymer composites can also be prepared by incorporating the aqueous polymer latex of the present invention as a binder or co-binder into the aqueous base formulation of a paint that already contains a TiO2 pigment, for example by mixing the aqueous polymer latex of the present invention with a pigment formulation that already contains further additives conventionally used in paint formulations.

[0067] In order to stabilize the TiO2 pigment particles in the aqueous pigment slurry or paste, the mixing may be optionally carried out in the presence of additives conventionally used in aqueous pigment slurries or pigment pastes, such as dispersants. Suitable dispersants include, but are not limited to, polyphosphates, such as sodium, potassium or ammonium polyphosphates, alkali metal and ammonium salts of homopolymers or copolymers of acrylic acid or maleic anhydride polymers, polyphosphonates, such as sodium 1-hydroxyethane-1,1-diphosphonate, and naphthalene sulfonates, especially their sodium salts.

[0068] The polymer concentration of the aqueous polymer latex used to prepare the aqueous dispersion of the polymer composite is generally in the range of 10% to 70% by weight, preferably 20% to 65% by weight, most preferably 30% to 60% by weight, in each case based on the total weight of the aqueous polymer latex.

[0069] In addition to the polymer latex and titanium dioxide pigment of the present invention and any conventional binders, the aqueous coating composition may contain one or more pigments different from the TiO2 pigment and / or filler.

[0070] Suitable pigments different from TiO2 pigments are, for example, inorganic white pigments, such as barium sulfate, zinc oxide, zinc sulfide, basic carbonates, antimony trioxide, lithopone (zinc sulfide + barium sulfate), or color pigments, such as iron oxide, carbon black, graphite, zinc yellow, zinc green, ultramarine, manganese black, antimony black, manganese violet, Prussian blue or Paris green. In addition to inorganic pigments, the emulsion paint of the present invention can also contain organic color pigments, such as sepia, gamboge, Cassel Brown, toluidine red, para red, Hansa yellow, indigo, azo dyes, anthraquinonoid and indigoid dyes, as well as dioxazine, quinacridone pigments, phthalocyanine pigments, isoindolinone pigments and metal complex pigments. Also suitable are synthetic white pigments with air inclusions to enhance light scattering, such as Ropaque® and AQACell® dispersions. Furthermore, the Luconyl® brands from BASF SE, such as Luconyl® Yellow, Luconyl® Brown and Luconyl® Red, especially the transparent versions, are also suitable.

[0071] Preferred fillers are selected from the group consisting of aluminosilicates such as feldspar, silicates such as kaolin, talc, mica and magnesite; alkaline earth metal carbonates such as calcium carbonate, magnesium carbonate and dolomite in the form of calcite or chalk; alkaline earth metal sulfates such as calcium sulfate, silicon dioxide, etc. Finely divided fillers are naturally preferred in the coating composition of the present invention. The fillers may be used in the form of individual components. In practice, however, filler mixtures such as calcium carbonate / kaolin, calcium carbonate / talc, etc. have been found to be particularly useful. Gloss paints generally contain only small amounts of very finely divided fillers or no fillers at all. Fillers also contain matting agents, which significantly impair the desired gloss. The matting agents are generally transparent and may be organic or inorganic. Examples of matting agents are inorganic silicates, such as the Syloid® brand of W.R. Grace & Company and the Acematt® brand of Evonik GmbH. Organic matting agents are available, for example, from BYK-Chemie GmbH under the Ceraflour® brand and also under the Ceramat® brand and from Deuteron GmbH under the Deuteron MK® brand.

[0072] The proportion of pigments and fillers in a coating composition can be described in a manner known per se by the pigment volume concentration (PVC), which is the ratio, expressed as a percentage, of the volume of pigment (VP) and filler (VF) to the total volume made up of the volumes of binder (VB), pigment (VP) and filler (VF) in the dried coating film: PVC=(VP+VF)×100 / (VP+VF+VB).

[0073] Preferably, the pigment volume concentration PVC of the coating composition of the invention is ≦35%.

[0074] In a further preferred embodiment, the wetting agent is selected from the group consisting of sodium, potassium or ammonium polyphosphates, the alkali metal and ammonium salts of acrylic acid or maleic anhydride copolymers, polyphosphonates, such as sodium 1-hydroxyethane-1,1-diphosphonate and naphthalenesulfonates, in particular the sodium salts thereof.

[0075] Suitable coalescing aids are, for example, Texanol or Optifilm from Eastman Chemical, and glycol ethers and esters available, for example, under the names Solvenon and Lusolvan from BASF SE, and Dowanol from Dow. The amount of coalescing aid is preferably less than 10% by weight, more preferably less than 5% by weight, based on the total formulation.

[0076] Suitable thickeners are, for example, associative thickeners, such as polyurethane thickeners. The amount of thickener is generally less than 5% by weight, more preferably less than 3% by weight, based on the total formulation.

[0077] Further formulation components for water-based coatings are described in detail in M. Schwartz and R. Baumstark "Water-based Acrylates for Decorative Coatings", Curt R. Vincentz Verlag, Hanover, 2001, p. 191-212 (ISBN 3-87870-726-6).

[0078] The coating composition may be applied to the substrate in a conventional manner, for example, by painting, spraying, dipping, rolling, bar coating.

[0079] In this case, the coating of the substrate is carried out in such a way that the substrate is first coated with the aqueous coating formulation according to the invention and then the aqueous coating is subjected to a drying step, in particular within a temperature range of from -10 to 50°C, advantageously from 5 to 40°C and particularly advantageously from 10 to 35°C.

[0080] The present invention is further illustrated by the following examples. EXAMPLES

[0081] In this example, the following components are used:

[0082] [Table 1]

[0083] Example E1 Binder based on a polymer with 2-octyl acrylate, n-butyl acrylate and methyl methacrylate A reactor equipped with stirrer, temperature control, nitrogen inlet and several inlets is charged with 244.3 g deionized water, 27.3 g polystyrene seed dispersion (33% by weight, particle size: 30 nm). The reaction mixture is purged with nitrogen and heated to 85° C. At 85° C., 5.0 g feed 2 is added. After 5 minutes, feed 1 and feed 2 are added in 180 minutes. Feed 1: 400.5 g deionized water, 18.5 g Dowfax 2A1, 20.8 g Rutensol TO 82, 6.9 g acrylic acid, 13.9 g acrylamide (50% by weight in water), 34.8 g 2-octyl acrylate, 349.0 g methyl methacrylate, 300.0 g n-butyl acrylate. Feed 2: 19.8 g aqueous sodium persulfate solution (7% by weight). The reaction mixture is post-polymerized at 85° C. for 30 minutes. Then Feed 3 and Feed 4 are added in 60 minutes. Feed 3: 6.9 g of aqueous t-butyl hydroperoxide (10% by weight). Feed 4: 6.2 g of aqueous Rongalit C (10% by weight). The reaction mixture is then cooled to ambient temperature and neutralized with sodium hydroxide to pH 8-9. Tg (dry dispersion): 21℃ Average particle size: 133 nm Solid content: 48.7% by weight

[0084] Example E2 Binder based on a polymer with 2-octyl acrylate, n-butyl acrylate and methyl methacrylate A reactor equipped with stirrer, temperature control, nitrogen inlet and several inlets is charged with 244.3 g deionized water, 27.3 g polystyrene seed dispersion (33 wt%, particle size: 30 nm). The reaction mixture is purged with nitrogen and heated to 85° C. At 85° C., 5.0 g feed 2 is added. After 5 min, feed 1 and feed 2 are added in 180 min. Feed 1: 400.5 g deionized water, 18.5 g Dowfax 2A1, 20.8 g Rutensol TO 82, 6.9 g acrylic acid, 13.9 g acrylamide (50 wt% in water), 69.5 g 2-octyl acrylate, 349.0 g methyl methacrylate, 265.0 g n-butyl acrylate. Feed 2: 19.8 g aqueous sodium persulfate solution (7 wt%). The reaction mixture is post-polymerized at 85° C. for 30 minutes. Then Feed 3 and Feed 4 are added in 60 minutes. Feed 3: 6.9 g of aqueous t-butyl hydroperoxide (10% by weight). Feed 4: 6.2 g of aqueous Rongalit C (10% by weight). The reaction mixture is then cooled to ambient temperature and neutralized with sodium hydroxide to pH 8-9. Tg (dry dispersion): 17℃ Average particle size: 132 nm Solid content: 48.0% by weight

[0085] Comparative Example C1 Binder based on a polymer with n-butyl acrylate and methyl methacrylate A reactor equipped with stirrer, temperature control, nitrogen inlet and several inlets is charged with 244.3 g deionized water, 27.3 g polystyrene seed dispersion (33% by weight, particle size: 30 nm). The reaction mixture is purged with nitrogen and heated to 85° C. At 85° C., 5.0 g feed 2 is added. After 5 minutes, feed 1 and feed 2 are added in 180 minutes. Feed 1: 400.5 g deionized water, 18.5 g Dowfax 2A1, 20.8 g Rutensol TO 82, 6.9 g acrylic acid, 13.9 g acrylamide (50% by weight in water), 349.0 g methyl methacrylate, 335.0 g n-butyl acrylate. Feed 2: 19.8 g aqueous sodium persulfate solution (7% by weight). The reaction mixture is post-polymerized at 85° C. for 30 minutes. Feed 3 and Feed 4 are then added in 60 minutes. Feed 3: 6.9 g of aqueous t-butyl hydroperoxide (10% by weight). Feed 4: 6.2 g of aqueous Rongalit C (10% by weight). The reaction mixture is then cooled to ambient temperature and neutralized with sodium hydroxide to pH 8-9. Tg (dry dispersion): 19℃ Average particle size: 132 nm Solid content: 48.1% by weight

[0086] Example E3 Semi-gloss paint formulation containing binder of Example E1 Mix 315.0 g of Kronos 4311 pigment with 15.0 g of water. At low stirring speed, add 1.75 g of AMP-95 neutralizer (Angus Chemical Co.), 5.0 g of propylene glycol (Univar), 2.0 g of Foamstar 2420 defoamer (BASF), 10.0 g of Tamol 165 A dispersant (Dow) and 3.0 g of Hydropalat WE 3320 wetting agent (BASF). At high stirring speed, add 1.5 g of Attagel 50 (BASF), 25.0 g of Minex 10 (Sibelco) filler and 20.0 g of Aquaflow NHS-310 (Ashland) nonionic associative thickener and mix for 30 minutes. Then add 105.8 g of deionized water and filter the mixture through a 400 μm filter. Then, 496.8 g of binder from Example E1, 25.0 g of Ropaque Ultra E polymer pigment (Dow), 2.0 g of Foamstar 2420 defoamer (BASF), 9.0 g of Texanol coalescent (Eastman) and 7.5 g of Optifilm 400 coalescent (Eastman) are added and mixed for 5 minutes. Then, 2.0 g of Proxel AQ biocide (Lonza), 3.0 g of Polyphase 663 fungicide (Troy Corporation) and 2.0 g of Rheolate CVS 10 nonionic associative thickener (Elementis) are added and mixed for 5 minutes. Finally, 2.0 g of Acrysol RM 895 nonionic associative thickener (Dow) and 3.5 g of water are added and the mixture is stirred at medium speed for 30 minutes.

[0087] Example E4 Semi-gloss paint formulation containing binder of Example E2 Mix 315.0 g of Kronos 4311 pigment with 15.0 g of water. At low stirring speed, add 1.75 g of AMP-95 neutralizer (Angus Chemical Co.), 5.0 g of propylene glycol (Univar), 2.0 g of Foamstar 2420 defoamer (BASF), 10.0 g of Tamol 165 A dispersant (Dow) and 3.0 g of Hydropalat WE 3320 wetting agent (BASF). At high stirring speed, add 1.5 g of Attagel 50 (BASF), 25.0 g of Minex 10 (Sibelco) filler and 20.0 g of Aquaflow NHS-310 (Ashland) nonionic associative thickener and mix for 30 minutes. Then add 96.3 g of deionized water and filter the mixture through a 400 μm filter. Then, 4.0 g of binder 50 from Example E2, 25.0 g of Ropaque Ultra E polymer pigment (Dow), 2.0 g of Foamstar 2420 defoamer (BASF), 9.0 g of Texanol coalescent (Eastman) and 6.0 g of Optifilm 400 coalescent (Eastman) are added and mixed for 5 minutes. Then, 2.0 g of Proxel AQ biocide (Lonza), 3.0 g of Polyphase 663 fungicide (Troy Corporation) and 2.0 g of Rheolate CVS 10 nonionic associative thickener (Elementis) are added and mixed for 5 minutes. Finally, 2.0 g of Acrysol RM 895 nonionic associative thickener (Dow) and 5.1 g of water are added and the mixture is stirred at medium speed for 30 minutes.

[0088] Comparative Example C2 Semi-gloss paint formulation containing binder of Example C1 Mix 315.0 g of Kronos 4311 pigment with 15.0 g of water. At low stirring speed, add 1.75 g of AMP-95 neutralizer (Angus Chemical Co.), 5.0 g of propylene glycol (Univar), 2.0 g of Foamstar 2420 defoamer (BASF), 10.0 g of Tamol 165 A dispersant (Dow) and 3.0 g of Hydropalat WE 3320 wetting agent (BASF). At high stirring speed, add 1.5 g of Attagel 50 (BASF), 25.0 g of Minex 10 (Sibelco) filler and 20.0 g of Aquaflow NHS-310 (Ashland) nonionic associative thickener and mix for 30 minutes. Then add 100.0 g of deionized water and filter the mixture through a 400 μm filter. Then, 3.0 g of binder 50 from Example C1, 25.0 g of Ropaque Ultra E polymer pigment (Dow), 2.0 g of Foamstar 2420 defoamer (BASF), 9.0 g of Texanol coalescent (Eastman) and 5.0 g of Optifilm 400 coalescent (Eastman) are added and mixed for 5 minutes. Then, 2.0 g of Proxel AQ biocide (Lonza), 3.0 g of Polyphase 663 fungicide (Troy Corporation) and 3.2 g of Rheolate CVS 10 nonionic associative thickener (Elementis) are added and mixed for 5 minutes. Finally, 1.5 g of Acrysol RM 895 nonionic associative thickener (Dow) and 5.4 g of water are added and the mixture is stirred at medium speed for 30 minutes. Abrasion resistance measured according to ASTM D2486: Number of scrapes before E3 coating breaks: 1411 Number of scrapes before E4 coating breaks: 1247 Number of scrapes before C2 coating breaks: 1158

[0089] The scratch resistance of Examples E3 and E4 is significantly improved compared to Example C2.

[0090] Gloss Measurement: Films were prepared on Leneta 3B black and white shielded drawdown cards using a 3 mil drawdown bar. Films were allowed to dry at room temperature for 24 hours. Gloss was measured with a glossmeter. The results were as follows: Gloss (20°) of coating of example E3: 8.4 Gloss (20°) of coating of example E4: 8.4 Gloss (20°) of coating of example C2: 7.7 Gloss (60°) of coating of Example E3: 42.2 Gloss (60°) of coating of Example E4: 42.3 Gloss (60°) of coating of Example E4: 40.8 Gloss (85°) of coating of Example E3: 81.8 Gloss (85°) of coating of Example E4: 81.7 Gloss (85°) of coating of Example C2: 80.9

[0091] The gloss of Examples E3 and E4 is improved compared to Example C2. Low shear viscosity measured according to ASTM D562: Low shear viscosity of E3 example coating (7 days after preparation): 96.2 KU Low shear viscosity of the coating of the example of E4 (7 days after preparation): 95.6 KU Low shear viscosity of the coating of Example C2 (7 days after preparation): 94.8 KU

[0092] Measuring opacity: Films were made on Leneta 3B black and white shielded drawdown cards using a 3 mil drawdown bar. Films were allowed to dry for 24 hours at room temperature. Opacity was determined spectrophotometrically as the ratio of light reflected from the dried coating on the black and white areas of the Leneta card. Opacity indicates the ability of the coating to hide a black surface. The results were as follows: Opacity of coating of Example E3: 97.52% Opacity of coating of Example E4: 97.53% Opacity of coating of Example C2: 97.51%

[0093] Aluminum and alkyd adhesion between coats measured according to ASTM D3359: equivalent for E3, E4 and C2 coatings.

[0094] Stain removal per ASTM D4828: Equivalent on E3, E4 and C2 coatings of pencil, lipstick, crayon, ballpoint pen, red wine, ketchup, coffee and mustard (assessed by visual inspection).

[0095] Determination of soil adhesion: The mill glaze on yellow pine wood is rubbed with water and allowed to dry overnight.

[0096] The substrate is divided into sections depending on the number of samples to be tested. Using an appropriate brush, apply the test paint samples at a natural spreading rate.

[0097] The coatings are allowed to cure at room temperature for 4 and 24 hours, respectively. Half of the coated area is then covered with 2 inches of dry soil (Arizona soil or carpet soil). The panel is allowed to sit for 15 minutes, then tilted vertically and tapped to remove the soil.

[0098] Lightly brush (15 strokes) the soiled areas of each sample.

[0099] Stain adhesion is comparable for the coatings of Examples E3, E4 and C2 (as assessed by visual inspection).

Claims

1. 1. An aqueous polymer latex obtained by polymerizing a monomer composition M by radical emulsion polymerization, optionally in the presence of a seed latex, said monomer composition M comprising, based on the total weight of said monomer composition M: a) 0.5 to 30% by weight of 2-octyl acrylate; b) 25 to 55% by weight of n-butyl acrylate; c) 35 to 65% by weight of methyl methacrylate; d) 0 to 5% by weight of one or more monoethylenically unsaturated carboxylic acids; e) 0 to 5% by weight of one or more monoethylenically unsaturated carboxylic acid amides, f) 0 to 10% by weight of one or more additional ethylenically unsaturated nonionic monomers different from monomers a), b), c), d), and e).

1. A water-based polymer latex comprising:

2. 2. The aqueous polymer latex of claim 1, wherein monomer d) is selected from the group consisting of acrylic acid, methacrylic acid and itaconic acid.

3. 3. The aqueous polymer latex of claim 1, wherein the monomer e) is selected from the group consisting of acrylamide and methacrylamide.

4. 4. The aqueous polymer latex according to claim 1, wherein monomer d) is present in an amount of 0.1 to 4% by weight.

5. 5. The aqueous polymer latex according to claim 1, wherein monomer e) is present in an amount of 0.1 to 4% by weight.

6. The monomer composition M is a) 1 to 15% by weight of 2-octyl acrylate; b) 25 to 55% by weight of n-butyl acrylate; c) 40 to 65% by weight of methyl methacrylate; d) 0 to 5% by weight of one or more monoethylenically unsaturated carboxylic acids; e) 0 to 5% by weight of one or more monoethylenically unsaturated carboxylic acid amides The aqueous polymer latex of claim 1 , comprising:

7. The monomer composition M is a) 3 to 12% by weight of 2-octyl acrylate; b) 30 to 50% by weight of n-butyl acrylate; c) 40 to 60% by weight of methyl methacrylate; d) 0.1 to 4% by weight of a monoethylenically unsaturated carboxylic acid selected from acrylic acid, methacrylic acid and itaconic acid; e) 0.1 to 4% by weight of monoethylenically unsaturated carboxylic acid amides selected from acrylamide and methacrylamide The aqueous polymer latex according to any one of claims 1 to 6, comprising:

8. The monomer composition M is a) 3 to 12% by weight of 2-octyl acrylate; b) 30 to 50% by weight of n-butyl acrylate; c) 40 to 60% by weight of methyl methacrylate; d) 0.5 to 3% by weight of acrylic acid; e) 0.5 to 3% by weight of acrylamide The aqueous polymer latex according to any one of claims 1 to 7, comprising:

9. 9. The aqueous polymer latex of any one of claims 1 to 8, wherein the monomer composition M is polymerized in the presence of 0.1 to 10 wt. %, based on the total weight of the monomer composition M, of a seed latex made of one or more ethylenically unsaturated monomers.

10. The seed latex is a copolymer of acrylic acid and C 2 ~C 10 -Alkyl ester, C of methacrylic acid 1 ~C 4 The aqueous polymer latex of claim 9, made with one or more ethylenically unsaturated monomers selected from the group consisting of alkyl esters and vinyl aromatic monomers.

11. 11. The aqueous polymer latex of any one of claims 1 to 10, wherein at least a portion of the 2-octyl acrylate is derived from renewable sources.

12. A copolymer contained in the aqueous polymer latex according to any one of claims 1 to 11.

13. i) an aqueous polymer latex according to any one of claims 1 to 11; ii) titanium dioxide pigment; 1. An aqueous coating composition comprising:

14. 14. The aqueous coating composition of claim 13, wherein the weight ratio of copolymer to said titanium dioxide pigment ranges from 0.1:5.0 to 5.0:0.

1.

15. 12. Use of the aqueous polymer latex according to any one of claims 1 to 11 as a binder in an aqueous coating composition containing titanium dioxide pigment.

Citation Information

Patent Citations

  • Use of a 2-octyl acrylate polymer as a binding agent in a coating composition

    WO2014207389A1

  • Aqueous polymer emulsion

    WO2016128574A1

  • Process for preparing an aqueous polymer latex

    WO2017191167A1

  • Aqueous polymer emulsion

    WO2018007325A1